Experimental investigations of colloid-associated metal mobility in mine-impacted wetland sediment - Colleen O. Harper; Richard T. Amos (Heliyon)
Metal mining operations can release toxic metals to surrounding environments where site-specific conditions control the movement of contaminants. Colloid-facilitated transport, the transport of contaminants with small, mobile particles, has been recognized as a potential contaminant transport vector in groundwater, but it remains unclear under what conditions it is important and whether neutral, metal-rich mine drainage from legacy mining impacts this transport vector. This work presents a set of laboratory column experiments that study the effect of colloids on metal mobility in saturated, wetland sediment that has been receiving neutral mine drainage for nearly a century, using mixed and single metal input solutions at neutral pH. Results indicate that colloid-facilitated transport is only important when small (<0.01 μm) colloids, most likely formed from organic matter, are present. Larger particles were found to be generally immobile, so could aid in the immobilization of metal contaminants. These findings imply that colloid-facilitated transport is an important transport vector in mine-impacted wetland sediment and should be considered when remediating mine sites.